Joining composites with adhesives : theory and applications - Wahab, Magd Abdel (Destech Publications, Inc., 2016)
Presented in this volume is a detailed scientific analysis of strategies for adhering composite materials to plastics, concrete, metals, and wood, as well as to other composites, using a variety of adhesives. The theory and analysis of composite bonding with adhesives are explained, along with information on adhesive formulation and selection, material preparation, joint geometry and joint design. Attention is given to how different types of adhered composite joints are empirically tested, e.g., for strength and under stress, and how models of joints with adhesives are developed. The book includes an intensive discussion of the uses of adhesives for composite repair. Part two focuses on applications of adhesive composite bonding in aircraft, automobiles, buildings, ships, railroads and dental restoration.
Keywords: Composite materials.; Adhesive joints.; Materials.; Materials science.; elektronické knihy; electronic books